2001
DOI: 10.7901/2169-3358-2001-2-935
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Aquatic Toxicity of Crude Oils

Abstract: Aquatic toxicity information is critical to provide scientifically defensible estimates of ecological impact and natural resource injury to aquatic organisms resulting from a petroleum spill. For most crude oils, the availability of aquatic toxicity information is a significant data gap. As part of Chevron's oil-specific properties summary sheet project, a series of marine fish (silversides, top smelt) and invertebrate (mysid shrimp) acute toxicity tests on five crude oils with extensive chemical analysis (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The M. beryllina PAH 45 LC50 (75.6 µg/L) in the present study was within the range of the PAH 41 inland silverside and topsmelt larvae 96‐h LC50s (30.3–128.2 µg/L) for 5 crude oils (Gala et al 2001). The PAH 45 LC50 (40.9 µg/L) for E. analoga from the present study was slightly higher than the range of Americamysis bahia 96‐h PAH 41 LC50s (19–36.2 µg/L) for 3 crude oils (Gala et al 2001). Vignier et al (2015) reported that the PAH 50 EC50 for oyster ( Crassostrea virginica ) embryo abnormality was 342 µg/L for Deepwater Horizon crude oil, similar to the M. edulis PAH 45 EC50 (381 µg/L) in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The M. beryllina PAH 45 LC50 (75.6 µg/L) in the present study was within the range of the PAH 41 inland silverside and topsmelt larvae 96‐h LC50s (30.3–128.2 µg/L) for 5 crude oils (Gala et al 2001). The PAH 45 LC50 (40.9 µg/L) for E. analoga from the present study was slightly higher than the range of Americamysis bahia 96‐h PAH 41 LC50s (19–36.2 µg/L) for 3 crude oils (Gala et al 2001). Vignier et al (2015) reported that the PAH 50 EC50 for oyster ( Crassostrea virginica ) embryo abnormality was 342 µg/L for Deepwater Horizon crude oil, similar to the M. edulis PAH 45 EC50 (381 µg/L) in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Although it is difficult to compare the present results with those of these older studies due to differences in analytical methods and exposure conditions, comparisons may be made with recent studies with other crude oils. The M. beryllina PAH 45 LC50 (75.6 µg/L) in the present study was within the range of the PAH 41 inland silverside and topsmelt larvae 96‐h LC50s (30.3–128.2 µg/L) for 5 crude oils (Gala et al 2001). The PAH 45 LC50 (40.9 µg/L) for E. analoga from the present study was slightly higher than the range of Americamysis bahia 96‐h PAH 41 LC50s (19–36.2 µg/L) for 3 crude oils (Gala et al 2001).…”
Section: Discussionsupporting
confidence: 81%